PACAP system evolution and its role in melanophore function in teleost fish skin. (15th August 2015) - Cardoso, João C.R.; Félix, Rute C.; Martins, Rute S.T.; Trindade, Marlene; Fonseca, Vera G.; Fuentes, Juan; Power, Deborah M.
Highlights: PACAP receptor genes duplicated and acquired distinct functions during the teleost radiation. PACAP receptor expression in tilapia skin is modified by a light/dark challenge. PACAP stimulates pigment aggregation in tilapia skin melanophores. PACAP activation of Pac1 a increases cAMP but RAMP1 attenuates the increase. Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP) administered to tilapia melanophores ex-vivo causes significant pigment aggregation and this is a newly identified function for this peptide in fish. The G-protein coupled receptors (GPCRs), adcyap1r1a (encoding Pac1 a) and vipr2a (encoding Vpac2 a), are the only receptors in melanophores with appreciable levels of expression and are significantly (p < 0.05) down-regulated in the absence of light. Vpac2 a is activated exclusively by peptide histidine isoleucine (PHI), which suggests that Pac1 a mediates the melanin aggregating effect of PACAP on melanophores. Paradoxically activation of Pac1 a with PACAP caused a rise in cAMP, which in fish melanophores is associated with melanin dispersion. We hypothesise that the duplicate adcyap1ra and vipr2a genes in teleosts have acquired a specific role in skin and that the melanin aggregating effect of PACAP results from the interaction of Pac1 a with Ramp that attenuates cAMP-dependent PKA activity and favours the Ca 2+ /Calmodulin dependent pathway.